Dokazna vrednost in dopustnost mnenja strokovnjaka - izvedenca v kazenskem postopku - Šepec, Miha (Pravnik, 2024)
An expert is a person who possesses special expertise required by the court during legal proceedings and is therefore commissioned to provide expert analysis to clarify the actual circumstances of the case. As an objective assistant to the court, the expert helps shape the course of criminal proceedings and influences the final decision. Consequently, the expert plays a crucial role in criminal proceedings. Unlike an ordinary witness, the expert’s work serves as a direct cognitive source of evidence. Their expertise not only provides knowledge of relevant facts but also assists the court in performing its judicial function. An expert, unlike a witness, has an active role: they can suggest the gathering of evidence, the provision of objects or data important for findings and opinions; if he is present during the viewing, reconstruction of the event or some other investigative act, he may suggest that individual circumstances be clarified or propose questions for interrogation. A fair criminal procedure is only possible if both the judge and the expert are impartial. The expert is not an assistant to any party but rather an assistant to the court in uncovering the truth. Experts are required to be not only knowledgeable but also objective and impartial. The principle of impartiality and independence that applies to the court also extends to experts. Therefore, any doubt on the impartiality of the expert raises doubts about the impartiality of the court and simultaneously threatens the equality of arms between the parties.
Keywords: criminal procedure; dokazi; due process; enakost orožij; equality of arms; evidence; expert; expert opinion; impartiality; izvedenci; kazenski postopek; nepristranost; pošten postopek; strokovno mnenje